Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 5 - Exponents and Polynomials - Chapters 1-5 Cumulative Review Problem Set - Page 233: 18



Work Step by Step

Using $a^{m}\times a^{n}=a^{m+n}$, we obtain: $(-6ab^{4})(-2b^{3})$ =$(-6\times-2)\times(a)\times(b^{4}\times b^{3})$ =$(12)\times (a)\times(b^{3+4})$ =$(12)\times(a)\times(b^{7})$ =$12ab^{7}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.